Synthesis of Some Novel Fluorinated/Nonfluorinated α-Amino Acids, Bearing 3-Thioxo-5-oxo-1,2,4-triazin-6-yl and Steroidal Moieties, and Evaluation of Their Amylolytic Effects against Some Fungi, Part-II - Reda M. Abdel-Rahman; Wafa A. Bawazir (Heteroatom Chemistry)
Some new fluorinated/nonfluorinated α-amino acids bearing 3-thioxo-5-oxo-1,2,4-triazin-6-yl and steroidal moieties have been obtained from condensation of the corresponding amino-triazinones with the steroid (Epiandrosterone). This was followed by the addition of HCN and, finally, acidic hydrolysis. The structure of the targets was established from their elemental analysis and spectral data. The amylolytic activity of the new products was evaluated against some fungi.